Diversity and Origin of the Central Mexican Alpine Flora - Victor W. Steinmann; Libertad Arredondo-Amezcua; Rodrigo Alejandro Hernández-Cárdenas; Yocupitzia Ramírez-Amezcua (Diversity, 2021)
Alpine vegetation is scarce in central Mexico (≈150 km2) and occurs on the 11 highest peaks of the Trans-Mexican Volcanic Belt (TMVB). Timberline occurs at (3700) 3900 m, and at 4750 m vascular plants cease to exist. The alpine vascular flora comprises 237 species from 46 families and 130 genera. Asteraceae (44), Poaceae (42), and Caryophyllaceae (21) possess 45% of the species; none of the remaining families have more than 10 species. Four species are strict endemics, and eight others are near endemics. Thirteen species are restricted to alpine vegetation but also occur outside the study area. Seventy-seven species are endemic to Mexico, 35 of which are endemic to the TMVB. In terms of biogeography, the strongest affinities are with Central or South America. Fifteen species are also native to the Old World. Size of the alpine area seems to not be the determining factor for its floristic diversity. Instead, the time since and extent of the last volcanic activity, in addition to the distance from other alpine islands, appear to be important factors affecting diversity. There is evidence for upward vegetational shifts having occurred during the last century.